THE NUMBER OF MISSING PERMANENT MOLAR TEETH BASED ON CHARACTERISTICS OF RESPONDENT ON LUBUK BUAYA PUBLIC HEALTH CENTER (Proceedings of the International Conference on Public Health, 2018)
Permanent molar are the teeth that mostly missing. In Padang, the Caries Index is 2.78, Missing-Teeth Index is 2.29, Missing Teeth Index percentage is 82.4% with 9.2% of denture usage.  Lubuk Buaya Public Health Center has the highest number of permanent tooth extraction in Padang. The purpose of this study is to look at the relationship of number of missing permanent molar teeth with the characteristics of respondent. The design of this study is using descriptive method. The number of samples are 97 respondents with age range between 25-44 years-old, who live in Lubuk Buaya Public Health Center working area that meet inclusion criteria.  About 90,7% of respondents lost 1-4 permanent molar while 9,3% respondents lost 5-8 molar. Most of male (84.6%) and female (97,8%) lost 1-4 molar teeth. Almost all of age range lost 1-4 molar. All respondent with only elementary school level of education lost 5-8 molar teeth, while other level of education lost 1-4 molar. Gender, age and the level of education affect the number of missing permanent molar teeth on Lubuk Buaya Public Health Center working area. Lower education level lead to the higher number of missing permanent molar teeth.
Keywords: permanent molar teeth, characteristics of respondent